Preliminary Comparative Investigations on Ballistic Properties of Intermediate Cartridges - Dawid Goździk; Bartosz FIKUS; Jacek KIJEWSKI (Problemy Mechatroniki)
The preliminary results of comparative investigations on intermediate cartridges were presented in this paper. The research focused mainly on the adopted assumptions and verification of research methods. Pressure ballistic test barrels, manufactured according to NATO EPVAT standards, were used for tests. The pressure courses of propellant gases in the barrel and the projectile velocity at four points of the bullet trajectory were measured. The pressure impulses, R100 parameter at 50 m and average bullet drag coefficient were calculated for each type of cartridge. The results allowed for a preliminary ballistic comparison of the most popular types of intermediate cartridges.